2021
DOI: 10.3390/biology10080746
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Rosa damascena Mill. and Rosa alba L. Essential Oils against the Multiplication of Herpes Simplex Virus Type 1 Strains Sensitive and Resistant to Acyclovir

Abstract: Background: The specific chemotherapeutics against herpes simplex virus type 1 (HSV) are nucleoside analogues such as acyclovir (ACV), but the most important problem is the formation of resistant mutants. The search for new therapeutic alternatives leads us to the purpose of investigating the effects of Rosa damascena Mill. and Rosa alba L. essential oils on the viral reproduction of susceptible (Victoria) and acyclovir-resistant (R-100) strains of HSV-1 replication in vitro, individually and in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Furthermore, another important consideration is that the IC50 of our analyzed products was very similar for the parental and mutated strains; therefore, they were able to elicit antiviral effects through a different mechanism than acyclovir. Very recently, other natural bioproducts, i.e., Rosa essential oils, have shown a very strong effect in interfering with the viral reproduction of both susceptible and resistant HSV-1 [26]. Here, the proposed mechanism is quite different from that of our formulations since the rose oils, added after the virus entered the cell together with acyclovir at a concentration four times lower than the IC50, considerably reduced the viral yield.…”
Section: Antiviral Activity Of the Three Formulations Against Acyclov...mentioning
confidence: 69%
“…Furthermore, another important consideration is that the IC50 of our analyzed products was very similar for the parental and mutated strains; therefore, they were able to elicit antiviral effects through a different mechanism than acyclovir. Very recently, other natural bioproducts, i.e., Rosa essential oils, have shown a very strong effect in interfering with the viral reproduction of both susceptible and resistant HSV-1 [26]. Here, the proposed mechanism is quite different from that of our formulations since the rose oils, added after the virus entered the cell together with acyclovir at a concentration four times lower than the IC50, considerably reduced the viral yield.…”
Section: Antiviral Activity Of the Three Formulations Against Acyclov...mentioning
confidence: 69%
“…When determining the effectiveness of the proposed interventions, five (3.65%) were shown not to be effective [ 84 , 107 , 126 , 131 , 139 ], three (2.19%) were somewhat effective [ 21 , 46 , 53 ], and 128 (93.43%) were effective as potential managements for resistant strains of HSV [ 1 - 3 , 6 - 20 , 22 - 45 , 47 - 52 , 54 - 56 , 58 - 83 , 85 - 106 , 108 - 125 , 127 - 130 , 132 - 138 ].…”
Section: Reviewmentioning
confidence: 99%
“…Of the papers reviewed, three (2.19%) papers displayed that nectin had efficacy as a second-line treatments in HSV [ 17 , 28 , 73 ], three (2.19%) papers showed efficacy using amenamevir [ 21 , 43 , 95 ], three (2.19%) using methanol extract were effective in various cell line [ 24 , 32 , 39 ], two (1.46%) using monoclonal antibodies [ 27 , 46 ], two (1.46%) with arbidol [ 75 , 81 ], two (1.46%) with siRNA swarms [ 22 , 98 ], two (1.46%) using Cucumis melo sulfated pectin were effective in Vero cells [ 10 , 123 ], two (1.46%) using components from Olea europeae were effective in Vero cells [ 125 , 130 ]. In addition to this, two (1.46%) with griffithsin (GRFT) were effective in various cell lines [ 45 , 80 ], two (1.46%) with Morus alba L. (compounds from mulberry root bark extract) were effective in Vero cells [ 85 , 103 ], two (1.46%) using nucleosides were effective in Vero cells [ 41 , 76 ], two (1.46%) with botryosphaeran were effective in Vero cells [ 74 , 128 ], two (1.46%) monoterpenes were effective in Vero cells [ 34 , 92 ], two (1.46%) with almond skin extracts were effective in Vero cells [ 26 , 68 ], two (1.46%) using bortezomib were effective in HCL and Vero cells [ 83 , 99 ], two (1.46%) using various flavonoid compounds [ 25 , 97 ], and two (1.46%) papers using essential oils were effective in Vero cells [ 31 , 34 ], but one (0.73%) showed that essential oils were not effective [ 131 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Rosa damascena also contains favonoids, such as kaempferol, quercetin, terpenes, tannins, and vitamin C [19][20][21], and its essential oil has been used as a natural medicine to treat infammation, coughs [19,22], and digestive problems [23]. Recently, Bulgarian rose damascena oil was reported to confer broad-spectrum antimicrobial activities, including antibacterial efects against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Escherichia coli [19,21], as well as antiviral activity [24]. In the present study, we investigated the antifungal efects of Bulgarian rose damascena oil against Candida albicans and Candida glabrata.…”
Section: Introductionmentioning
confidence: 99%